Alliance Politics Amid the BJP's Rise: More Continuity than Change in 2019. (December 2019) - Ziegfeld, Adam
Pre-election alliances have long figured prominently in Indian elections. Has the politics surrounding pre-election alliances changed with the rise of the Bharatiya Janata Party (BJP)? This article analyzes patterns of election alliance formation across India's states and examines the extent to which these alliances affected the outcome of the 2019 election. It finds that patterns of alliance formation in the run-up to the 2019 election did not, on the whole, differ noticeably from prior elections. Though the BJP's strong performance muted the impact of some key alliances, election alliances nevertheless had a perceptible impact on the final allocation of seats and appear to have influenced voting behaviour largely as anticipated.